Contextualizing abstraction and abstract expressionist art in Malaysia - Abdullah, Sarena (Department of Southeast Asian Studies, University of Malaya Kuala Lumpur, Malaysia, 2013)
Abstract Expressionism has been one of the Western art movements that has influenced Malaysian artists. Since late 1950s and even until today, abstraction and works that falls into the formalistic approach of Abstract Expressionist have been well accepted and produced and this is more so since the promulgation of the National Cultural Policy in 1971 and the Islamization Policy in the late 1970s. This paper discusses abstraction and Abstract Expressionism and their acceptance, adaptation, and transformation under local conditions and situations. This could be observed as abstraction and Abstract Expressionism were used as a stylistic approach or an artistic method to highlight local subject matter and personal experiences by Malaysian artists through works that render local landscapes and nature, themes and religion and/or cultural references such as Jawi script, myths and mythologies and the abstraction of figuration. This paper will also discuss how works that seem to be rooted in formalistic exploration flourished aligned to this condition. Within this framework, this paper will discuss several works that have been recognized and discussed as abstract and Abstract Expressionist works produced by Malaysian artists.